2014
DOI: 10.1128/aem.01021-14
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Virulence-Associated Genes and Genetic Relationships in Non-O1/O139 Vibrio cholerae Aquatic Isolates from China

Abstract: e Non-O1/O139 Vibrio cholerae is naturally present in aquatic ecosystems and has been linked with cholera-like diarrhea and local outbreaks. The distribution of virulence-associated genes and genetic relationships among aquatic isolates from China are largely unknown. In this study, 295 aquatic isolates of V. cholerae non-O1/O139 serogroups from different regions in China were investigated. Only one isolate was positive for ctxB and harbored a rare genotype; 10 (3.4%) isolates carried several types of rstR seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
6
32
1
3
Order By: Relevance
“…Our findings differ from the relatively rare detection of these two putative virulence factors in environmental isolates worldwide (13,44). Given the role of NAG-ST in severe diarrheal disease in human volunteers reported previously by Morris et al (9), the widespread distribution of this pathogenic factor in non-O1/non-O139 V. cholerae in the Chesapeake Bay should be noted by public health authorities.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our findings differ from the relatively rare detection of these two putative virulence factors in environmental isolates worldwide (13,44). Given the role of NAG-ST in severe diarrheal disease in human volunteers reported previously by Morris et al (9), the widespread distribution of this pathogenic factor in non-O1/non-O139 V. cholerae in the Chesapeake Bay should be noted by public health authorities.…”
Section: Discussioncontrasting
confidence: 83%
“…In some cases, these factors are accompanied by rtxA cytotoxic activity, causing mammalian cells to detach and round up (7). In our analysis, hlyA, hap, and rtxA were common virulence factors, with frequencies similar to those reported by environmental surveillance studies in Argentina (15), Iceland (19), Italy (23), Bangladesh (20), and China (13). Almost ubiquitous in this study was the V. cholerae type 6 secretion system, with 76% of the isolates carrying all three genes (vasAKH).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The serotype O1 has been further divided into the classical (CL) and El Tor (ET) biotypes (21,22). The pathogenicity of V. cholerae depends on a combination of properties, including the presence of cholera toxin (CT), encoded by ctxA, and the colonization and adhesion factor encoded by tcpA (22,23). Studies have shown seasonal patterns for this species, with increased occurrence and incidence of wound infections at warmer temperatures (24).…”
mentioning
confidence: 99%
“…Unfortunately, there are no genome sequence-based data for recombination in environmental strains, but several MLST studies on environmental strains have shown high diversity, indicating high recombination rates, which have also been supported by several additional criteria (44)(45)(46). Each of these referenced studies used strains with a sampling bias toward human-associated strains in countries with often inadequate treatment of sewage, adding the complication that some of the "environmental" strains were from fecal contamination.…”
Section: Significance Of the Asian Homeland-middle East-makassar Migrmentioning
confidence: 99%